THE METHOD OF COMMITTING CRIME AS NECESSARY ELEMENT OF CORPUS DELICTI - Khurramovich, Khudaykulov Feruzbek (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
The article widely uses logical, inductive, deductive, systematic, logical-legal, comparative-legal research methods. In particular, among the signs of the objective side of the crime, the method of committing the crime has its own importance, and any crime is committed in a certain way. The method of committing a crime is a form of external expression of a socially dangerous act, and in most cases, the legislator considers the method as a necessary or aggravating sign of the crime in the criminal legislation. The analysis of the articles of the Special part Criminal Code shows that the method of committing a crime is expressed by the legislator in two forms in the criminal law. The first is as a form of a socially dangerous act, while the second is considered independently. As an example of the first, articles 110, 118, 119, 164 of the Criminal Code can be given. In the disposition of these articles, words such as